Legal arrangements related to animal welfare in turkey - Aşkın Yaşar; Serdar İzmirli (Eurasian Journal of Veterinary Sciences)
Subject of animal welfare has been considered and discussed since the beginning of 1960s in different parts of the world which has result the acceptance of "Universal Declaration of Animal Rights". Now a days, many significant developments and legal regulations have been declared about animal welfare by Organizations in EU and other member countries. It was observed that there are arrangements for animals producing for meat, milk, leather, wool, egg and animals bred for sportive purposes in a farm and also for animals bred for experiment and scientific studies in the frame of animal welfare regulations. First law issued in this scope in Turkey is Animal protection Act no 5199. Humanitarian criterions in lots of subjects such us ownership, maintenance and transportation of animals were tried to be established in the Act. Some legal arrangements related with animal welfare such as breeding, transportation, slaughtering and killing and usage with experimental and scientific purposos of animals, have been being tried lo obtain in the draft "Veterinary Frame Act" prepared jointly with EC under the section entitled as "Animal Welfare". Acts and regulations of animal welfare in force and in draft stage in Turkey which are related with farm animals, pet and companion animals and experimental animals shall be discussed in this study. In this frame, there are seven legal regulations of farm animals, six legal regulations of pet and companion animals and five legal regulations of experimental animals which are in force was determined.